ANALISIS PELAKSANAAN PERAWATAN TALI PUSAT TERBUKA PADA BAYI BARU LAHIR DI PUSKESMAS SILAPING KABUPATEN PASAMAN BARAT TAHUN 2020 - Ainal Mardiah (HUMAN CARE JOURNAL, 2021)
ABSTRACTThe incidence of infection has the largest contribution to the infant mortality rate in Indonesia after low birth weight (LBW). The number of mothers giving birth in 2020 were 383 mothers, with 8 neonatal deaths. The umbilical cord is the main route of entry for systemic infection in the newborn.The purpose of this study was to analyze The Implementation of Open Umbilical Cord Care in Newborns at Silaping Community Health Center, Ranah Batahan District, West Pasaman Regency in 2020. It was qualitative with a in-depth interviews design. The informants were 1 coordinating midwife, 1 child program holder, 2 implementing midwives and 2 mothers. The instrument used in in-depth interviews with a voice recorder, observation sheets and documentation. The results of in-depth interviews found that there was no written policy regarding the implementation of open umbilical cord care, but open umbilical cord care had been carried out to every newborn by midwives and socializing to new mothers when they return home. The existence of umbilical cord care opened properly and it was useful for babies to minimize the risk of infection from umbilical cord injuries but there were still people or mothers who have given birth to wrap the umbilical cord because they were still in doubt afraid of infection. This research is expected to provide information and as a monitoring of the implementation of the implementation of open umbilical cord care in newborns